EDUKASI ORANGTUA DAN GURU DALAM MENCIPTAKAN LINGKUNGAN YANG MENDUKUNG KEMANDIRIAN ANAK - Aisyah; Isabella Hasiana (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program aims to increase the role of parents and teachers in creating an environment that supports children's independence. Independence is a crucial aspect in children's development that allows them to develop the skills of self-regulation, decision making and responsibility. This activity was carried out in a kindergarten in the city of Surabaya. The method used in this program is providing counseling and assistance to parents and teachers. The results of this program show that the awareness and ability of parents and teachers to support children's independence. This program concludes that close collaboration between parents and teachers is the key to creating an environment conducive to the development of children's independence. Continuous support and provision of practical skills to parents and teachers has proven effective in achieving this goal. Recommendations for future programs include expanding coverage to more schools and communities and developing more comprehensive training modules.